THE CHARACTERISTICS OF RISK FACTORS ASSOCIATED WITH LEUKORRHEA IN FEMALE STUDENTS - Shalma Alya Fadilla; Atika, Atika (UNIVERSITAS AIRLANGGA, 2024)
Background : The importance of reproductive health awareness for women, as women are vulnerable to infectious diseases. One of the reproductive health problems is leukorrhea, which is the discharge of genital fluid that is not blood but is often ignored. In fact, leukorrhea can be fatal if left untreated. According to WHO, around 90% of Indonesian women are at risk of developing leukorrhea. This is due to the tropical climate in Indonesia, which supports the growth of fungi, one of the causes of leukorrhea. Method: This study used an observational analytic approach with a cross-sectional research design. The sample size was 131 female students, who were selected by total sampling. The independent variables in this study were age, BMI, stress level, vulva hygiene knowledge, and vulva hygiene behavior. Data analysis was performed using Chi-square, Mann-Whitney, and logistic regression tests Result: The results showed that the most common age was 20 years (23.7%), 76 people (58%) had a normal BMI, and 61 people (46.6%) had been living in the boarding school for 1 year. Most of the female students experienced moderate stress (46 people, 35.11%), 114 (87.02%) had good vulva hygiene behavior, 94 (71.75%) had good vulva hygiene knowledge, and 109 (83.20%) had leukorrhea. The Mann-Whitney test results showed a relationship between the incidence of leukorrhea and age (p = 0.001), the Chi-square test results showed a relationship between the incidence of leukorrhea and stress level (p = <0.001), BMI (p = 0.344), vulva hygiene knowledge (p = 0.088), and vulva hygiene behavior (p = 1.000). Conclusion: Age and stress level were associated with the incidence of leukorrhea, and stress level was the most associated factor with the incidence of leukorrhea in female students at the Pondok Pesantren Mahasiswa Khoirul Huda Surabaya, Indonesia.